Tobacco industry interference against the single stick cigarette sales ban - Kandeepan, S.; Perera, M.; Wijesuriya, H.; Perera, C.S.; Rajasuriya, M. (European Publishing, 2021)
Introduction: Sri Lanka implemented 80% Pictorial Health Warnings and is planning to implement standardised packaging. However, a considerable proportion of smokers buy cigarettes in the loose form. Sale of cigarettes as single sticks promotes smoking among minors, beginners and poor due to high affordability and accessibility. In September 2018, Health Minister proposed to ban sale of single sticks as recommended by the Framework Convention on Tobacco Control. The proposal failed to gain Cabinet approval preventing its implementation. Objectives:This study aimed to explore the tobacco industry’s tactics in sabotaging the proposed ban on single stick sale of cigarettes in Sri Lanka.Methods: Investigative research techniques were used. Content analysis was carried out on identified web posts and documents to determine the tobacco industry’s strategic involvement, their front groups and arguments used. Results: First argument, the ban would reduce government tax revenue due to reduction of cigarette sales, was made by three parties: cigarette industry, media and Minister of Finance (MoF). The strongest advocate against the ban was the Tobacco Retailer’s Association (TRA), backed by the Ceylon Tobacco Company (CTC). TRA’s argued that retail business would be impacted, again because of reduced sales. TRA directly advocated MoF via a meeting. Third argument, used by the MoF was that the ban would increase beedi use. The cabinet rejected the ban as MoF and three other ministers opposed. Conclusion(s):CTC successfully interfered in the ban on single sticks cigarette sale through the TRA, media and the MoF, arguing that resulting reduced cigarette sales would generate a negative impact.
Keywords: pictorial health warnings; single stick cigarettes; framework convention on tobacco control